(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluated the effects of two rabbit genotypes of Chinchilla (CH×CH; n = 18) and New Zealand White (NZW×NZW; n = 10) and two dietary energy levels (2800 kcal ME/kg [E1] and 3000 kcal ME/kg [E2]) on post-weaning production performance, morphometric traits, and economic indices. A 2 × 2 factorial experiment was implemented using two genotypes (CH×CH and NZW×NZW) and two dietary energy levels (E1 and E2) with three replications in a completely randomized design. Analysis of variance indicated significantly (p < 0.05) higher initial body weight (IBWT) (388.90 ± 3.99 cm), final head-to-shoulder length (FHTSL) (11.43 ± 0.26 cm), and final hind leg length (FLHL) (16.10 ± 9.10 cm) in favour of the interaction between the NZW×NZW genotype and the E2 diet. The NZW×NZW genotype in comparison with the CH×CH, exhibited significantly (p < 0.05) higher IBWT (377.63 g vs. 239.35 g), final body weight (742.42 g vs. 416.73 g), total weight gain (364.79 g vs. 177.38 g), average daily feed intake (13.03 g vs. 7.16 g), and several morphometric traits. The NZW×NZW genotype also significantly (p < 0.05) outperformed the CH×CH in revenue (₦1635.77 vs. ₦740.85) and gross margin (₦1424.65 vs. ₦820.45). Whereas the E2 diet resulted in significantly higher IBWT, the energy level had no significant effect (p > 0.05) on the economic indices. The interaction of NZW×NZW genotype and E2 energy level diet was most effective in enhancing production performance, conformation traits and economic returns, and is recommended for profitable rabbit production.